2021
DOI: 10.3889/oamjms.2021.5813
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Properties of Recombinant Human Erythropoietin in the Wound Healing

Abstract: BACKGROUND: Erythropoietin (EPO) is the main stimulator of erythropoiesis, but EPO also has non-hematopoietic effects. The recent data show the positive effects of EPO on tissue regeneration. AIM: This review aims to know highlights the pathophysiological mechanisms of EPO at different stages of tissue regeneration, and possible clinical applications in wound healing. METHODS: A review of the literature considering reviews, clinical studies, original papers, and articles from electronic data has been used. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Tobalem et al [ 62 ] also informed a dose-dependent positive effect of systemic EPO early treatment reducing inflammation and accelerating healing of burn wounds. Toleubayev et al [ 63 ] also stated a positive effect of EPO in several wound healing models, for instance traumatized wounds, infected wounds, chronic ischemic wounds, and diabetic ones where EPO significantly reduced tissue inflammation and accelerated the blood vessels regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Tobalem et al [ 62 ] also informed a dose-dependent positive effect of systemic EPO early treatment reducing inflammation and accelerating healing of burn wounds. Toleubayev et al [ 63 ] also stated a positive effect of EPO in several wound healing models, for instance traumatized wounds, infected wounds, chronic ischemic wounds, and diabetic ones where EPO significantly reduced tissue inflammation and accelerated the blood vessels regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The activation, migration, and proliferation of endothelial cells, as well as the maturation of cell junctions and the surrounding basement membrane, all contribute to the development of new functional capillary structures. VEGF influences each of these phases [14]. Hence, indirectly, giving erythropoietin can trigger the emergence of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoietin is a glycoprotein hormone that can stimulate angiogenesis [11]. Various studies have been conducted to prove that the administration of erythropoietin accelerates the speed of wound healing [12], [13], [14]. In 2010, Hamed et al found that topical erythropoietin treatment quadrupled the speed of wound repair in diabetic rats with full-thickness wounds and reduced cell apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing is a natural physiological response to tissue damage. In general, wound healing is performed with four specific stages of hemostasis, inflammation, proliferation, and maturation (Figure 1) [8][9][10]. ECM plays a crucial role in every step of the wound healing process.…”
Section: Introductionmentioning
confidence: 99%